2014
DOI: 10.1021/jp504976s
|View full text |Cite
|
Sign up to set email alerts
|

Control of Nanostructural Dimension by Crystallization in a Double-Crystalline Syndiotactic Poly(4-methyl-1-pentene)-block-poly(l-lactide) Block Copolymer

Abstract: The control of nanostructural dimension by crystallization-induced chain stretching was investigated in a novel double-crystalline block copolymer, syndiotactic poly(4-methyl-1-pentene)-block-poly(L-lactide) (sPMP−PLLA), featuring a lamellar phase. Because of the similar glass transition temperatures of sPMP and PLLA, their blocks could crystallize under soft confinement (i.e., a crystallization temperature higher than the glass transition temperatures of the constituent blocks) in sPMP−PLLA. With the strong s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 67 publications
1
12
0
Order By: Relevance
“…In our experiment mode, it is expected that the LAM-1 structure should exhibit no scattering pattern. Similar phenomena are widely reported in the literature for the sheared LAM structure when the X-ray passes through the sample along the gradient direction. , However, in this work, a perfect orientation of the LAM-1 structure is difficult to achieve since we just used a flat spoon to scrap the sample unidirectionally. Therefore, very few lamellae in the LAM-1 structure are still edge-on arranged, leading to the weak scattering arcs along the equatorial direction in Figure a.…”
Section: Resultssupporting
confidence: 61%
“…In our experiment mode, it is expected that the LAM-1 structure should exhibit no scattering pattern. Similar phenomena are widely reported in the literature for the sheared LAM structure when the X-ray passes through the sample along the gradient direction. , However, in this work, a perfect orientation of the LAM-1 structure is difficult to achieve since we just used a flat spoon to scrap the sample unidirectionally. Therefore, very few lamellae in the LAM-1 structure are still edge-on arranged, leading to the weak scattering arcs along the equatorial direction in Figure a.…”
Section: Resultssupporting
confidence: 61%
“…4), where the growth direction of PCL crystals controls the final crystal orientation at each d PCL . It is also reported using other crystalline-crystalline diblock copolymers that the existing crystalline lamellar morphology significantly affects the subsequent crystallization of block chains with T c,2 [57,59,60,64,66,67,[70][71][72]. In addition, it is reasonable to suppose that the crystallization behavior and crystal orientation of block chains with T c,2 depend significantly on the hardness of pre-existing crystalline lamellar morphology, because the crystallization of block chains confined in hard nanolamellae is extremely different from that in soft nanolamellae (Figs.…”
Section: Sequential Crystallization Of Crystalline-crystalline Diblocmentioning
confidence: 90%
“…The sequential crystallization has been examined using several crystalline-crystalline diblock copolymers with sufficiently separate crystallizable temperatures [56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72]. We examined the crystallization behavior and crystal orientation of PCL blocks in PCL-block-polyethylene (PCL-b-PE) diblock copolymers [56,58,[61][62][63]65,69], where the PCL blocks (with T c,2 $ 40°C) were accommodated between the crystalline lamellar morphology provided by the advance crystallization of PE blocks (with T c,1 $ 100°C), and started to crystallize there.…”
Section: Sequential Crystallization Of Crystalline-crystalline Diblocmentioning
confidence: 99%
“…The crystallization behavior of several crystalline−crystalline (di-and triblock) copolymers has been studied. 24,25,43,44 It has been reported that if the melting temperatures for both blocks in a double-crystalline polymer are similar, both blocks can crystallize together from the melt for symmetric block ratios. As a consequence, the final morphologies of the block copolymer are more complicated due to the interactive effect of the microphase separation, crystallization, vitrification, and sequence of crystallization.…”
Section: ■ Introductionmentioning
confidence: 99%